ANALISIS ISI BUKU PEGANGAN PAUD MELALUI PERSPEKTIF PENDEKATAN SAINTIFIK - Fatimatuz Zahro dan Indayati (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2016)
Education can not run without some components of education and learning in learning process. Components of education consist of learning environment, teacher, student, learning resources, and learning process. One of the learning resources used in the early childhood education is handbook (in magazine). Is magazine using a latest curriculum that adopted scientific approach method or not. Research is conducted using a learning teory from Piaget, Brunner, and Vygotsk. They said that learning is process. Method of this research is library reserach, “Dino” magazine published by CV. Dipo Mulyo as the primary data. Data is collected from the magazine using documentary study. Author uses content analysis and inductive method for data analysis. The result of this study is that in the handbook (magazine) “Dino” published by CV. Dipo Mulyo used a scintific approach as like 2013 curriculum.